The IMPLEMENTASI PERATURAN WALI KOTA KEDIRI NOMOR 16 TAHUN 2020 TENTANG PENGENDALIAN KEGIATAN HIBURAN DAN PERDAGANGAN DALAM RANGKA PERCEPATAN PENANGANAN CORONA VIRUS DISEASE 2019 - Sultan Sahara; Suwarno; Teguh Pramono (stiatabalong.ac.id, 2023)
The policy set by the Kediri City Government since the beginning of the Covid-19 pandemic did not carry out a “lock down” because they wanted the community's economy to continue. The Mayor of Kediri on May 18 2020 stipulated Mayor of Kediri Regulation Number 16 of 2020 Concerning Control of Entertainment and Trade Activities in the Context of Accelerating Handling of Corona Virus Disease 2019. The Kediri City Government has stipulated the obligation to implement health protocols, limit operating hours and business activity visitors. The research method used is qualitative, the data presentation is descriptive with a case study approach. The focus of the research is to analyze the implementation of regulations with the concept of George C. Edward III which has 4 (four) variables namely; communication, resources, disposition and bureaucratic structure. The data sources are primary and secondary data. The sampling technique is purposive sampling. Data collection technique; structured and unstructured interviews, documentation, observation. data validity; triangulation. The results of the research analysis are as follows: 1) Policy communication variables from the transmission and clarity dimension are good, the constraints are on the consistency dimension. 2) The resource variables from the dimensions of human resources, information, authority and facilities are good. 3) The disposition variable experiences problems in the disposition effect dimension, carrying out bureaucratic arrangements; well, the incentive dimension; had problems. 4) Variable good bureaucratic structure. SOP; well, fragmentation; good. The implementation of public policy has encountered obstacles, namely that there are still many people violating health protocols, traders are still not in order, there are people who have the wrong paradigm regarding the Covid-19 virus, a reduction in employee wages causes violations of business operating hours.